2008
DOI: 10.1002/cne.21727
|View full text |Cite
|
Sign up to set email alerts
|

Glycine receptor‐mediated synaptic transmission regulates the maturation of ganglion cell synaptic connectivity

Abstract: It is well documented that neuronal activity is required for the developmental segregation of retinal ganglion cell (RGC) synaptic connectivity with ON and OFF bipolar cells in mammalian retina. Our recent study showed that light deprivation preferentially blocked the developmental RGC dendritic redistribution from the center to sublamina a of the IPL. To determine whether OFF signals in the visual stimulation are required for OFF RGC dendritic development, the light evoked responses and dendritic stratificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 106 publications
(25 reference statements)
3
39
0
Order By: Relevance
“…The AB5405 antibody targets the last 38 amino acids of the human M/LWS opsin C-terminus and specifically labels cone photoreceptors in rabbit and chicken (see Xu and Tian, 2008;Yan et al, 2009). In a fish, the sea lamprey (Petromyzon marinus), AB5405 labeled the outer segment of the long (cone-like) photoreceptor (Muradov et al, 2008) which has a long wavelength visual pigment with absorbance peak at 600 nm (Hárosi and Kleinschmidt, 1993).…”
Section: Immunohistochemistrymentioning
confidence: 98%
“…The AB5405 antibody targets the last 38 amino acids of the human M/LWS opsin C-terminus and specifically labels cone photoreceptors in rabbit and chicken (see Xu and Tian, 2008;Yan et al, 2009). In a fish, the sea lamprey (Petromyzon marinus), AB5405 labeled the outer segment of the long (cone-like) photoreceptor (Muradov et al, 2008) which has a long wavelength visual pigment with absorbance peak at 600 nm (Hárosi and Kleinschmidt, 1993).…”
Section: Immunohistochemistrymentioning
confidence: 98%
“…A21311, RRID: AB_10058149) was used to enhance fluorescent signals of YFP-expressing RGCs. This antibody was raised against GFP isolated directly from Aequorea Victoria and has been characterized by immunocytochemistry in granule cells (Overstreet-Wadiche et al, 2006), olfactory sensory neurons (Levai et al, 2003), hippocampal neurons (Huang et al, 2005) and retinal ganglion cells (Xu and Tian, 2007; 2008) that express GFP or YFP. A polyclonal antibody against tyrosine hydroxylase (TH) (Chemicon AB1542, RRID: AB_90755) was used to label TH positive dopaminergic amacrine cells in the retina.…”
Section: Methodsmentioning
confidence: 99%
“…RGCs display cell subtype specific dendritic morphologies, with over a dozen distinctive RGC subtypes performing a range of functional duties in parallel visual processing (Masland, 2001, Sun et al, 2002a; Kong et al, 2005; Coombs et al, 2006; Völgyi et al, 2009). Accumulating evidence indicated that the dendritic ramification of RGCs in different sublaminae of the inner plexiform layer (IPL) is achieved, at least partially, through vision dependent dendritic refinement (Tian and Copenhagen, 2003; Liu et al, 2007; Xu and Tian, 2007; 2008; Tian 2011; Burnat et al, 2012). However, it remains controversial whether acquisition of the coverage territory and dendritic density (the branching pattern) of RGCs requires visual stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that also GlyR isoforms, consisting from and subunits are involved in the regulation of cellular diVerentiation. Analyzing the adult Spastic mouse mutants, in which the OFF signal transmission in the rod pathway is largely blocked due to a reduction of GlyR-expression, Xu and Tian (2008) showed that these mice had altered retinal ganglion cell (RGC) light-evoked synaptic inputs from ON and OFF pathways. The spastic mutation also blocked the developmental redistribution of RGC dendrites from the center to sublamina of the inner plexiform layer, suggesting that visual stimulation regulates the maturation of RGC synaptic activity and connectivity primarily through GlyRmediated synaptic transmission (Xu and Tian 2008).…”
Section: Excitatory Glyr Function and Cellular Signalingmentioning
confidence: 99%
“…Analyzing the adult Spastic mouse mutants, in which the OFF signal transmission in the rod pathway is largely blocked due to a reduction of GlyR-expression, Xu and Tian (2008) showed that these mice had altered retinal ganglion cell (RGC) light-evoked synaptic inputs from ON and OFF pathways. The spastic mutation also blocked the developmental redistribution of RGC dendrites from the center to sublamina of the inner plexiform layer, suggesting that visual stimulation regulates the maturation of RGC synaptic activity and connectivity primarily through GlyRmediated synaptic transmission (Xu and Tian 2008). In addition, GlyR and GABA A receptors might act in concert, as it was shown that both agonist glycine and GABA contribute to the regulation of neurite outgrowth in developing spinal cord neurons (Tapia et al 2001).…”
Section: Excitatory Glyr Function and Cellular Signalingmentioning
confidence: 99%